Predictors of postoperative recurrence in locally advanced gastric cancer patients achieving pathological complete response after neoadjuvant therapy: a matched case-control study - Jiang, Zhiqiang; Lyu, Jiankai; Cong, Xiliang; Xu, Na; Bai, Ziyan; Zhao, Zhouyi; Fu, Siyun; Ma, Baozhen; Zhao, Lingdi (Frontiers in Oncology, 2026)
BackgroundAchieving a pathological complete response (pCR) after neoadjuvant therapy is a favorable prognostic factor in locally advanced gastric/gastroesophageal junction cancer. However, recurrence still occurs in a subset of these patients. This study aimed to identify clinical factors associated with recurrence in patients who attained pCR.MethodsThis retrospective study included 16 patients with recurrence early after achieving pCR. Each case was matched with two controls (non-recurrence) based on age and sex. Clinical characteristics were compared, and factors with P ≤ 0.1 in univariate analysis were included in a subsequent multivariate logistic regression analysis to identify independent predictors.ResultsUnivariate analysis identified significant differences between recurrence and non-recurrence groups in tumor grade, neoadjuvant therapy regimen, PD-L1 expression, and preoperative CEA levels. Multivariate analysis established clinical T stage and neoadjuvant regimen as independent prognostic factors for recurrence. Specifically, compared to patients with cT4 stage and those receiving neoadjuvant chemotherapy, patients with cT3 stage (P=0.035) and those receiving neoadjuvant chemoimmunotherapy (P=0.009) had a significantly lower risk of recurrence.ConclusionAchieving pCR does not guarantee cure. Clinical T stage and neoadjuvant regimen were independent risk factors for recurrence. Identifying high-risk patients among those with pCR was crucial for tailoring personalized surveillance and adjuvant strategies.